Myocardial Fibrosis and Prognosis in Heart Transplant Recipients - Hughes, Andrew (Circ Cardiovasc Imaging, 2019)
BACKGROUND: Myocardial fibrosis is a well-described histopathological feature in heart transplant recipients. Whether myocardial fibrosis in heart transplant recipients is independently associated with clinical outcomes is unclear. We sought to determine whether myocardial fibrosis on late gadolinium enhancement cardiovascular magnetic resonance imaging (LGE CMR) in heart transplant recipients was independently associated with all-cause death or major adverse cardiac outcomes in the long term. METHODS: Using a cohort of consecutive heart transplant recipients that had CMR, we determined the prevalence and the patterns of myocardial fibrosis and analyzed associations between myocardial fibrosis and a composite endpoint of all-cause death or major adverse cardiac events (MACE): retransplantation, non-fatal myocardial infarction, coronary revascularization, and heart failure hospitalization. RESULTS: One hundred and fifty-two heart transplant recipients (age, 54±15 years; 29% women; 5.0±5.4 years after heart transplantation) were included. Myocardial fibrosis was present in 18% (37% infarct pattern, 41% non-infarct pattern, and 22% both). Its prevalence was positively associated with cardiac allograft vasculopathy (CAV) grade. With a median follow-up of 2.6 years, myocardial fibrosis was independently associated with all-cause death or MACE (hazard ratio [HR], 2.88; 95% confidence interval [CI] 1.59–5.23; p<0.001) after adjustment for CAV, history of rejection, time since transplantation, left ventricular ejection fraction (LVEF), and indexed right ventricular end-diastolic volume (RVEDVI). Every 1% increase in myocardial fibrosis was independently associated with a 6% higher hazard for all-cause death or MACE (HR, 1.06; 95% CI, 1.03–1.09; p<0.001). The addition of myocardial fibrosis variables to models with CAV, history of rejection, time since transplantation, LVEF, and RVEDVI resulted in significant improvements in model fit, suggesting incremental prognostic value. CONCLUSIONS: In heart transplant recipients, myocardial fibrosis is seen on LGE CMR in 18%. Both the presence and the extent of myocardial fibrosis are independently associated with the long-term risk of all-cause death or MACE.